State of knowledge about autism spectrum disorders among residents of Szczecin - preliminary report - Maciejewska, Martyna; Janik, Inga; Fabian-Danielewska, Anna; Korabiusz, Katarzyna; Wawryków, Agata; Wilczyńska, Agnieszka; Stecko, Monika (Journal of Education, Health and Sport, 2018)
Introduction: Autism spectrum disorders are more often diagnosed. Like any disorder, autism can cause discomfort, even distress to families. Thanks to educational campaigns, more people know what this disorder is related to. Therefore, it is worth checking what the society’s knowledge of autism is. Research goal: Describing the state of knowledge about autism spectrum disorders among residents of Szczecin. Conclusion: The subjects showed great knowledge about the autism spectrum. The fact of an earlier contact with a person with an autism spectrum disorder or a member of her family does not in any way relate to the knowledge of the subjects on this disorder. Women received higher results in the questionnaire.